From Epic Tragedy to Tragic Epic: Marina Carr’s Hecuba, Girl on an Altar, and iGirl - Salomé Paul (ABEI Journal, 2023)
This article examines the genre of “epic tragedy” in two of the most recent adaptations of Greek tragedy by Marina Carr, Hecuba (2015) and Girl on an Altar (2022), as well as its reversal to produce a “tragic epic” in iGirl (2021). In the Poetics, Aristotle establishes a stark distinction between the genres of epic and tragedy. Yet, this distinction has been challenged throughout history in dramatic practices – in Euripides and Shakespeare’s tragic plays for instance – and theories – most notably by the emergence of epic theatre coined by Bertolt Brecht. Drawing from all these traditions, this article highlights Carr’s process of “epicisation” of tragedy through the implementation of a new form of dramatic speech and dramatisation of a narrative rather than a plot in Hecuba and Girl on an Altar. These strategies have influenced the creation of iGirl, which is a postmodern epic brought on stage through the lens of tragedy.